Implementasi Pembelajaran E-Learning Sebagai Transformasi Pendidikan di Era Digital - Verawati, Usnida Junaeka; Alifa, Yanuar Dila Nur; Millah, Zahrotul; Nissa, Zulfa Khoirun (Social Science Academic, 2023)
The purpose of this study is to find out the Implementation of E-Learning as an Educational Transformation in the Digital Age. The method used is a qualitative method with a descriptive approach. The results of this study show that E-Learning as an educational transformation in the digital era has an important role in improving student learning outcomes. The implementation of E-Learning learning as an educational transformation in the digital era includes the use of various learning models, in the form of Distance learning, Hybrid learning, Blended learning, and Transformation theory. The implementation of e-learning brings several benefits, including wider access to education, cost savings and the ability to tailor learning to individual needs. But there are also various challenges such as limited internet access, technological readiness and reduced social interaction.